Integrating Pain Treatment into Your Spine Practice - Falowski, Steven M.; Pope, Jason E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
.
Part One Identification and Management of Pain Patients -- Chapter 1 Identification of the Pain Patient -- Chapter 2 Role of Spinal Surgery in Pain Management -- Chapter 3 Failed Back Surgery Syndrome -- Chapter 4 Cervical Pain Syndromes -- Chapter 5 Revision Surgery and Alternative Treatment Options for Recurrent Pain -- Chapter 6 Considerations for Neuromodulation -- Part Two Integrating Pain into Practice -- Chapter 7 Practice Setup -- Chapter 8 Referral Networks -- Chapter 9 Integration of Specialties -- Chapter 10 Coding and Reimbursement for Spinal Cord Stimulation -- Part Three Pain Management Therapies -- Chapter 11 Medications Used for the Treatment of Back Pain -- Chapter 12 Interventional Procedures -- Chapter 13 Neuromodulation -- Chapter 14 Intrathecal Therapy for Chronic Spine Pain -- Part Four Surgical Pain Therapies -- Chapter 15 Epidural Paddle Placement for Spinal Cord Stimulation -- Chapter 16 Percutaneous Placement -- Chapter 17 Peripheral Nerve Stimulation - Cervical Syndromes -- Chapter 18 Peripheral Nerve Stimulation for Axial Pain Syndromes -- Chapter 19 Intrathecal Drug Delivery: Surgical Technique -- Chapter 20 Vertebroplasty and Kyphoplasty -- Chapter 21 Emerging Technology in Neuromodulation: Waveforms and New Targets in Spinal Cord Stimulation. .
Keywords: Medicine; Neurosurgery; Orthopedics; Pain medicine; Medicine & Public Health; Pain Medicine; Neurosurgery; Orthopedics; Electronic books